2020
DOI: 10.2196/21933
|View full text |Cite
|
Sign up to set email alerts
|

Public Emotions and Rumors Spread During the COVID-19 Epidemic in China: Web-Based Correlation Study

Abstract: Background Various online rumors have led to inappropriate behaviors among the public in response to the COVID-19 epidemic in China. These rumors adversely affect people’s physical and mental health. Therefore, a better understanding of the relationship between public emotions and rumors during the epidemic may help generate useful strategies for guiding public emotions and dispelling rumors. Objective This study aimed to explore whether public emotions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
(24 reference statements)
0
42
0
Order By: Relevance
“…Excessive health information might heighten the perceived impact of the pandemic through cyberchondria that is defined as the unfounded escalation of concerns about COVID-19 symptoms based on a review of search results and literature online 43 . According to the nocebo phenomenon 21 , conflicting health information (e.g., confused face mask policy) 22 , unproven conspiracy theories 44 and rumors 45 also enhanced the negative impact of the pandemic. In contrast, people who were likely to less frequently accessed health information were less anxious, depressed and stressed, and worried about the pandemic 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive health information might heighten the perceived impact of the pandemic through cyberchondria that is defined as the unfounded escalation of concerns about COVID-19 symptoms based on a review of search results and literature online 43 . According to the nocebo phenomenon 21 , conflicting health information (e.g., confused face mask policy) 22 , unproven conspiracy theories 44 and rumors 45 also enhanced the negative impact of the pandemic. In contrast, people who were likely to less frequently accessed health information were less anxious, depressed and stressed, and worried about the pandemic 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The high risk and uncertainty of the emerging infectious disease were likely to cause widespread public concern. Its suddenness and the insufficiency of the official response inevitably caused an information vacuum [ 60 ], which provided a breeding ground for rumors [ 46 , 61 ]. Due to geographical social distancing, rumor resolution mainly relied on online rebuttal.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research studies on public sentiment during major public health emergencies found that people usually exhibited negative sentiments, such as panic, anxiety, anger, sadness, and disgust [ 44 , 45 ]. After rumors were refuted, public sentiment usually changed from negative to positive [ 46 , 47 ]. However, Zollo et al [ 16 ] found that negative sentiments dominated in the comments on Facebook that refuted conspiracy theories, regardless of users’ polarization.…”
Section: Introductionmentioning
confidence: 99%
“…The practical concerns about using apps may also get more complicated with the psychology behind using (or not using) any apps [53][54][55][56][57][58][59]. In a recent publication, Williams et al [53] reported that the participants in their study were not sure whether using digital contact tracing was a good idea.…”
Section: Psychological Aspectsmentioning
confidence: 99%
“…In one study, for instance, although the information and technology use kept the participants informed and connected, they experienced negative emotional consequences, including stress, worry, and anxiety, and reported varying degrees of preparedness [54]. In addition, rumors spread may influence public's emotions, increasing their anxiety and anger [55]. Furthermore, isolation and quarantine during the pandemic seem to be associated with interpersonal sensitivity, somatization, and distress, especially symptoms like suspiciousness, hostility, and fearful thoughts of losing autonomy as well as feelings of inadequacy, uneasiness, and discomfort during interpersonal interactions [56].…”
Section: Psychological Aspectsmentioning
confidence: 99%